A de novo complex chromosome rearrangement (CCR) involving chromosome 5, 6 and 15 - Candeias, Cristina (2013)
Abstrat publicado em: Chromosome Research. 2003;21(Suppl 1):S1–S168. doi:10.1007/s10577-013-9364-x